3D Nickel Skeletons as Ultrabroadband Terahertz Absorbers. (6th September 2021) - Yang, Peidi; Dai, Mingcong; Xiong, Hongting; Hao, Sibo; Zhang, Weihao; Zhang, Baolong; Ouyang, Chen; Li, Qiao; He, Feng; Miao, Jungang; Wu, Xiaojun
Abstract: Recent advances in terahertz (THz) absorbing materials and technology show futuristic potentials for practical applications in THz radars and telecommunications, stealth and shielding. However, the lack of versatile materials naturally working in this specific electromagnetic wave region with simultaneously featuring high absorption efficiencies, ultrabroad bandwidths, low‐costs, good stabilities, and flexibilities, is impeding the proliferation of real THz disruptive applications. Here a kind of flexible structure material, 3D nickel (Ni) skeleton, fabricated from an electroplating sintering method with irregular pore distribution makes possible the successful realization of a highly absorbing response for ultrabroadband THz waves due to the effective combination of both material and structural absorption mechanisms. 3D Ni skeletons with 90 ppi nonuniform pore‐size ranges enable >99% absorption capabilities in the frequency range of 0.5–2.0 THz independent on both the THz incidence angles and polarizations. Experimental validation of THz shielding implemented on both 100 GHz and 4.3 THz video imaging systems corroborates the highly efficient absorbing with frequency expansibility. Such capabilities are further verified on millimeter‐wave security checkers for 32–36 GHz. This prototypical demonstration lays the foundation for the next‐generation THz absorbing technology, accelerating advanced THz technologies toward practical applications. Abstract : Wu group demonstrates for the first time that 3D metal skeletons can be used as highly efficient, ultrabroadband, cost‐effective, environment friendly, and flexible terahertz (THz) and millimeter wave absorption materials. This research provides an opportunity for developing next‐generation THz absorbing materials and technology, accelerating advanced THz technologies toward practical applications.